The Influence of Population Agglomeration on the Upgrading of the Industrial Structure — Evidence from China - Lu, Yang; Zhang, Jie (International Journal of Business, Economics and Management, 2022)
As an important component of economic, social, and industrial development, changes in the labor force affect a country’s economic development in terms of fiscal expenditure, consumption structure, and production capacity, which also promote or inhibit the upgrading of the overall industrial structure and internal structure. Based on the inter-provincial panel data of 30 provinces, autonomous regions, and municipalities (excluding the Tibet Autonomous Region) in mainland China from 2010 to 2019, this paper conducts an empirical analysis of the impact of population agglomeration on the upgrading of the industrial structure and the contribution rate of tertiary industry output value in different regions. We conclude: (1) Generally speaking, population agglomeration has the effect of promoting the upgrading of the industrial structure. (2) The impact of population agglomeration on the industrial structure is different in different regions, hindering the upgrading of the industrial structure in eastern provinces, having no significant impact on the western region, and encouraging the upgrading of the industrial structure of central provinces. (3) Concerning the tertiary industry, population agglomeration significantly promotes the contribution rate of the tertiary industry output value in different regions. Therefore, the following suggestions are put forward: (1) Promote the reform of the household registration system. (2) Increase investment in human capital.